Rotational thromboelastometry and patient blood management: A narrative review - Elham Khalaf-Adeli; Fatemeh Tobeyani (Asian Journal of Transfusion Science)
Limitation of standard coagulation tests in early detection of coagulopathy leads to empirical decision-making for the management of the coagulopathy, which in many cases is accompanied by improper transfusion. Some studies have investigated the role of rotational thromboelastometry (ROTEM) in reducing the need for blood products in different clinical conditions, which have been associated with different results. Whether ROTEM as a point of care test reduces the need for transfusion in all clinical settings is still a question. A brief introduction of methodology of ROTEM and its role in patient blood management (PBM) approach is explored in this review. Search was performed to find literature describing ROTEM applied for decrease in transfusion requirements. Specific search terms were “Thromboelastometry,” “ROTEM,” “Cardiac surgical procedures,” “Trauma,” “wounds and injuries” “Liver transplantation,” “obstetric” “Transfusion,” and “PBM.” we reached to 75 publications for this review after application of our search strategy. The number of publications in the field of obstetric was insufficient for review and conclusion. The available evidence supports the helpfulness of ROTEM test in reducing the need for blood transfusions in surgery or trauma. However, it is need to further investigation to evaluate the benefit and efficacy of ROTEM in other medical conditions such as obstetric hemorrhage.